Real-time interleaved spectroscopic photoacoustic and ultrasound (PAUS) scanning with simultaneous fluence compensation and motion correction - Jeng, Geng-Shi; Li, Meng-Lin; Kim, MinWoo; Yoon, Soon Joon; Pitre, John J.; Li, David S.; Pelivanov, Ivan; O’Donnell, Matthew (Nature communications, 2021)
For over two decades photoacoustic imaging has been tested clinically, but successful human trials have been limited. To enable quantitative clinical spectroscopy, the fundamental issues of wavelength-dependent fluence variations and inter-wavelength motion must be overcome. Here we propose a real-time, spectroscopic photoacoustic/ultrasound (PAUS) imaging approach using a compact, 1-kHz rate wavelength-tunable laser. Instead of illuminating tissue over a large area, the fiber-optic delivery system surrounding an US array sequentially scans a narrow laser beam, with partial PA image reconstruction for each laser pulse. The final image is then formed by coherently summing partial images. This scheme enables (i) automatic compensation for wavelength-dependent fluence variations in spectroscopic PA imaging and (ii) motion correction of spectroscopic PA frames using US speckle tracking in real-time systems. The 50-Hz video rate PAUS system is demonstrated in vivo using a murine model of labelled drug delivery. Spectroscopic photoacoustic imaging has been limited by wavelength-dependent fluence variations and tissue motion. Here, the authors achieve real-time fluence and motion correction in vivo by using a wavelength-tunable laser, sequential scan of a narrow beam and partial image reconstruction for each pulse.